Neurological development of congenital heart disease in the neonatal period (Research, Society and Development, 2022)
Congenital heart diseases are often surgically corrected during childhood, and this procedure is becoming increasingly common in the neonatal period due to the high mortality rate caused by this pathology in newborns. The first 28 days of life are decisive for the growth and development of a child, and when patients with congenital heart disease at this age are submitted to this type of surgery, the whole process may trigger impacts and even complications in the neurological development of these patients. This review aimed to understand what these problems are and their incidence in these newborns in the short and long term, through a systematic literature review of publications from 2017 to 2022, in Portuguese, English and Spanish. A survey was conducted in the PubMed and SciELO databases. It is noticed that there are few studies on the neuropsychomotor system affected after surgery for correction of congenital heart disease, a reality that needs to be changed in order to obtain better prognoses in neonates requiring this intervention.